Assessing the safety of sitagliptin in older participants in the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS) - Bethel, M; Engel, S; Green, J; Huang, Z; Josse, R; Kaufman, K; Standl, E; Suryawanshi, S; Van de Werf, F; McGuire, D; Peterson, E; Holman, R; et al. (American Diabetes Association, 2017)
Objective Limited data exist regarding safety and efficacy of antihyperglycemic drugs in older patients with type 2 diabetes. The Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS) was a randomized, double-blind, placebo-controlled trial assessing the impact of sitagliptin on a primary composite outcome of cardiovascular death, nonfatal stroke, nonfatal myocardial infarction, or unstable angina hospitalizations in patients with type 2 diabetes (HbA1c ≥6.5% [48 mmol/mol] and ≤8.0% [64 mmol/mol]) and cardiovascular disease. We analyzed baseline characteristics and clinical outcomes for TECOS participants aged ≥75 years. Research Design and Methods Clinical and safety event summaries are presented for older versus younger participants and for the treatment groups within the older cohort. Results Of 14,351 participants with age recorded, 2004 (14%) were ≥75 years old (mean [SD] age 78.3 [3.1] years), with 68% men and median (IQR) type 2 diabetes duration 12.0 (7, 21) years. During 2.9 years’ median follow-up, older participants had higher rates of the primary outcome (6.46 vs. 3.67 events per 100 person-years; HR [95% CI] 1.72 [1.52–1.94]), death (2.52 [2.20–2.89]), severe hypoglycemia (1.53 [1.15–2.03]), and fractures (1.84 [1.44–2.35]). In the older cohort, sitagliptin did not significantly impact the primary composite (1.10 [0.89–1.36]), death (1.05 [0.83–1.32]), heart failure hospitalization (0.99 [0.65–1.49]), severe hypoglycemia (1.03 [0.62–1.71]), rates of acute pancreatitis and pancreatic cancer, or serious adverse events. Conclusions Among older patients with well-controlled type 2 diabetes and cardiovascular disease, sitagliptin had neutral effects on cardiovascular risk and raised no significant safety concerns.